PHENOTYPIC DETECTION OF METALLO BETA LACTAMASE PRODUCING PSEUDOMONAS AERUGINOSA IN WOUNDS - SANDHYA RANI T; SWATHI.S (International Journal of Pharma and Bio Sciences, 2015)
Pseudomonas aeruginosa, an important opportunistic pathogen causing a wide range of acute and chronic infections.The present study was undertaken to detect the Metallo β lactamase in isolated of Pseudomonas aeruginosa which was isolated from wound infection and evaluated their susceptibility patterns.The presence of the MBL enzyme was detected by phenotypic confirmatiory tests are IMIPENEM-EDTA combined disc synergy test and Imipenem EDTA double disk synergy test .Out of 161 sample which were culture 39(24.2%)yielded the growth of Pseudomonas aeruginosa. Among the 39 Pseudomonas aeruginosa isolates 14(35.8%) were MBL produced P.aeruginosa and were also resistant to Ceftazidime/Clavulonic acid (CAC),Ceftazidime(CAZ), Amikacin(AK),Ciprofloxacin(CIP),Gentamicin(GEN).In our study out of 39 isolates, 14(35.4%) isolates are resistant to carbapenem and confirmed by disk potentiation test. The early detection may help in appropriate antimicrobial therapy and avoid the multidrug resistant strains.we recommend a routine surveillance on antibiotic resistance in every clinical microbiology laboratory in order to aid infection control.